THE ANALYSIS OF THE IMPLEMENTATION OF THE NATIONAL HEALTH INSURANCE FRAUD PREVENTION PROGRAM - Safitri, Auliya; Karlinda; Nurcihikita, Tiara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
The National Health Insurance (JKN) Program The National Health Insurance (JKN) organized by the Social Security Administration Agency (BPJS) Kesehatan is one of the Indonesian government's strategic efforts to realize an inclusive and equitable health system for all people. This program faces various serious challenges, one of which is the problem of fraud or fraud. This study aims to analyze the implementation of fraud prevention programs in JKN, identify the obstacles faced, and evaluate the effectiveness of the strategies implemented. This research is qualitative using a systematic review approach technique. The article used in this study is a full article text with an observational study design published from 2016 to 2024. Independent variables include the national health insurance insurance program, and the dependent variable, namely insurance fraud fraud . Article data collection is carried out by searching for articles on Google Scholar, ProQuest, and Science Direct database search databases. The Indonesian state has formed an anti-fraud team, but it has not functioned optimally due to the lack of knowledge about fraud prevention in the JKN program. There are still many who have not implemented the prevention program (FRAUD) optimally, from various programs in Indonesia.